HUBUNGAN KETERSEDIAAN PANGAN DAN KETERATURAN PENERIMAAN RASKIN DENGAN STATUS KETAHANAN PANGAN RUMAH TANGGA PENERIMA RASKIN - Santi Santi; Dini Ririn Andrias (Media Gizi Indonesia, 2015)
Food availability is one of the subsystem that should be fullﬁ led in order to achieve good household food security.  Regularity of subsidized rice receipt was expected to help the poor to fulﬁ ll the need of their staple foods stockperiodically. The purpose of this study was to analyze association between food availability and regularity of subsidized rice receipt to household food security among subsidized rice for the poor recipient households. This study was an observational analytic research using cross sectional design. Forty-two households who received subsidized rice for the poor in Tompokersan village, Lumajang regency were selected using simple random sampling technique. Data analyzed by Spearman Correlation test. The result showed that the household was insecure without hunger (47.6%) and there was association between regularity of subsidized rice receipt to household food security status (p = 0.002 and r = 0.458). Conversely, there was no association between food availability and household food security status (p= 0.071). The conclusion of this study was regularity of subsidized rice receipt could increase household food security status. Recommendations that can be given are monitor the schedule of subsidized rice and striving for the subsidized rice to be able to regularly accepted.Keywords: food availability, household food security, subsidized rice